AD, Volume 29, n° 3, 2004 - Full Issue - journal system (Africa Development, 2022)
Contents Cultivating Conflict: Agricultural 'Betterment', the Native Land Husbandry Act (NLHA) and Ungovernability in Colonial Zimbabwe, 1951-1961 Guy Thompson ......................................1 Informing Approaches in Establishing stand Alone Community Literacy Programmes in South Africa Chris Kanyane ........................................40 The Determination and Analysis of Constraints Resource Use Efficiency in Multiple Cropping System by Small-Holder Farmers in Ebonyi State, Nigeria Michael U. Awoke & Eugene C. Okorji ..........................58 The Challenge of the Participatory Approach to Rural Poverty Alleviation: The Example of Olugbena Group of Villages, Ewekoro Local Government of Ogun State, Nigeria Adetoye Faniran & Thompson Aina Adeboyejo ...................70 Informal and Formal Sector Inter-linkages and the Incidence of Poverty in Nigeria: A Case Study of Ilorin Metropolis Gafar T. Ijaiya & Chika A. Umar. .................................84 The Status of Yorùba Dialects in Communicative Competence and Language Proficiency Felix Abidèmi Fabùnmi ...................................103 Mothers in the Informal Economy and Changes in Child feeding and Caring Roles in Kampala, Uganda Innocent Najjumba Mulindwa & James P. M. Ntozi ................114 Book Reviews/Revues de livres Arnfred Signe (ed) Re-thinking Sexualities in Africa, Uppsala: Nordic Africa Institute Amanda Gouws ................................131 Adekeye Adebajo, Building Peace in West Africa: liberia , Sierra Leone and Guinea Bissau. Boulder: Lynne Rienner, 2002 Samuel Ong'wen Okuro .......................134